Impact of the Pro12Ala Polymorphism of the PPAR-Gamma 2 Gene on Metabolic and Clinical Characteristics in the Palestinian Type 2 Diabetic Patients. (22nd October 2009) - Ereqat, S.; Nasereddin, A.; Azmi, K.; Abdeen, Z.; Amin, R.
Abstract : Peroxisome proliferators activated receptor-gamma2 (PPARγ 2) represents the transcriptional master regulator of adipocyte differentiation and therefore has been suggested as a candidate gene for obesity, insulin resistance, and dyslipidemia. The objective of the study was to investigate for the first time the potential association of the most common variant Pro12Ala (p.P12A) substitution of the PPAR γ 2 gene with body mass index (BMI), blood pressure, fasting plasma glucose, plasma total cholesterol, LDL and HDL cholesterol, and plasma triglyceride in a sample of 202 (138 females and 64 male) type 2 diabetic Palestinians. Genotyping of the PPAR γ 2 p.P12A polymorphism was determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis. The A12 allele was associated with lower fasting plasma glucose (P = .03 ) but had no influence on blood pressure, BMI, or other metabolic parameters. In obese patients, the p.P12A substitution was associated with elevated total plasma cholesterol levels (P = .02 ) and a tendency toward increased LDL cholesterol level (P = .06 ). In conclusion, the p.P12A variant of the PPAR γ 2 may influence cardiovascular risk through effects on lipid metabolism in obese T2D Palestinian patients.